The Characteristics of Vilnius Ukrainian National Community Media Consumption on the Case of the War in Ukraine - Visockytė, Monika (Žurnalistikos tyrimai, 2017)
The objective of the publication is to investigate what are the daily characteristics of media consumption of Vilnius Ukrainian national community and how do these characteristics vary on the case of the War in Ukraine as well as the role of the media in shaping the political identity and opinion of Vilnius Ukrainian national community. The tasks of analysis: to clarify how Vilnius Ukrainian national community uses the media; to analyse how the consumption of the media of Vilnius Ukrainian national community vary on the case of the War in Ukraine; to clarify how media contributes to the shape of political opinion of Vilnius Ukrainian national community; Having analysed the academic literature and done the quantitative and qualitative researches, it was concluded that the characteristics of media consumption of Vilnius Ukrainian national community are typical to the characteristics of media consumption of national communities that form their identity in contemporary and global media surroundings. Vilnius Ukrainian national community consumes media in Lithuanian, Ukrainian, English and Russian. This proves why the political identity of contemporary national communities is rotational. The political identity of contemporary national communities that live in European countries as well as Ukrainian national community is related not with a particular country but with values of a democratic government. When the War in Ukraine started the need of information in Vilnius Ukrainian national community increased. The need of the information of Ukrainian media increased while the information of Lithuanian media was consumed to get in touch with the daily news related with the War in Ukraine. This indicates that Vilnius Ukrainian national community uses the information of different countries for different purposes.